2016
DOI: 10.1186/s11671-016-1508-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Neurotoxicity of Metallic Nanoparticles the Cascades of Oxidative Stress?

Abstract: With the rapid development of nanotechnology, metallic (metal or metal oxide) nanoparticles (NPs) are widely used in many fields such as cosmetics, the food and building industries, and bio-medical instruments. Widespread applications of metallic NP-based products increase the health risk associated with human exposures. Studies revealed that the brain, a critical organ that consumes substantial amounts of oxygen, is a primary target of metallic NPs once they are absorbed into the body. Oxidative stress (OS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 122 publications
(120 reference statements)
0
47
1
1
Order By: Relevance
“…Numerous studies have implicated mitochondrial dysfunction and oxidative stress damage in the neurotoxicity of metallic NPs. [50][51][52][53] Chen et al reported that nano-alumina particles could target mitochondria, causing changes in mitochondrial membrane potential and cellular oxidation levels. 54 High doses of nano-silica resulted in damage to mitochondria and inhibition of mitochondrial biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have implicated mitochondrial dysfunction and oxidative stress damage in the neurotoxicity of metallic NPs. [50][51][52][53] Chen et al reported that nano-alumina particles could target mitochondria, causing changes in mitochondrial membrane potential and cellular oxidation levels. 54 High doses of nano-silica resulted in damage to mitochondria and inhibition of mitochondrial biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vivo studies have revealed that AgNPs, administered through intravenous injection, oral administration (van der Zande et al, ), intranasal instillation (Wen et al, ) and intraperitoneal injection (Daniel, Tharmaraj, Sironmani, & Pitchumani, ) can be absorbed and detected in many organs including, kidney, liver, lungs, spleen and brain (Song et al, ; Tang et al, ). Once located in the organs they generate ROS, which leads to cellular dysfunction via OS (Anna et al, 2015; AshaRani et al, ; Braydich‐Stolle et al, ; Choi et al, ; Gonzales, Lison, & Kirsch‐Volders, ; Guo et al, ; Guo et al, ; Han et al, ; Heidary, Ghasemi, Zijoud, & Ranjbar, ; Hussain, Hess, Gearhart, & Schlager, ; Kim et al, ; Lee et al, ; Patlolla, Hacckett, & Tchounwou, ; Song et al, ). Ag displays a strong affinity for thiol (‐SH) groups in biomolecules found in the body.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of ROS is induced, directly or indirectly, by NPs; ROS plays an important role in genotoxicity via OS. Oxidation of DNA involves mutagenesis, carcinogenesis, neurodegenerative diseases, aging, cell signaling, and lipid peroxidation leading to cell death, apoptosis and carcinogenesis (Song et al, ). The purpose of this review is to compile data on AgNPs from the available literature and their role in various biological actions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to small molecules inhibitors, nanoinhibitors can achieve stronger inhibition efficacy, longer circulation, and better amyloid targeting. However, most of the reported nanoinhibitors are prepared based on metallic nanoparticles, which may induce neurotoxicity [40]. Non-metallic nanoparticles such as carbon dots (C-dots) might be a more appropriate choice for amyloid inhibitors.…”
Section: Sers Probes Have Been Used For Bio-imaging Applications Suchmentioning
confidence: 99%